2018
DOI: 10.1016/j.cmi.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Adverse birth outcomes associated with Zika virus exposure during pregnancy in São José do Rio Preto, Brazil

Abstract: Although other studies have associated many newborn outcomes to ZIKV infection during pregnancy, these same adverse outcomes were rare or nonexistent in this study. The clinical presentation the newborns we studied was mild compared to other reports, suggesting that there is significant heterogeneity in congenital Zika infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 22 publications
5
67
1
6
Order By: Relevance
“…ZIKV-positive urine is a transient occurrence (Zhang et al 2016) and may have been no longer present in some of the positive cases. Our findings complement previous investigations highlighting the variable consequences for newborns of having a mother who is ZIKV-positive (Wheeler et al 2018) as well as the occurrence of adverse neurological consequences in babies whose mothers did not have detectable ZIKV during their gestation (Nogueira et al 2018). The rates of detection of ZIKV in maternal or neonatal urine in our study population is consistent with what has been reported previously (Gourinat et al 2015) and is most likely a consequence of the transient nature of ZIKV infection at this site (Zhang et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…ZIKV-positive urine is a transient occurrence (Zhang et al 2016) and may have been no longer present in some of the positive cases. Our findings complement previous investigations highlighting the variable consequences for newborns of having a mother who is ZIKV-positive (Wheeler et al 2018) as well as the occurrence of adverse neurological consequences in babies whose mothers did not have detectable ZIKV during their gestation (Nogueira et al 2018). The rates of detection of ZIKV in maternal or neonatal urine in our study population is consistent with what has been reported previously (Gourinat et al 2015) and is most likely a consequence of the transient nature of ZIKV infection at this site (Zhang et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Reports 3,11,12 regarding the prevalence of microcephaly and adverse birth outcomes found that these ranged from 3-4% in Rio de Janeiro and 5-42% in the USA. A 2017 study 13 in São Paulo, Brazil, found adverse outcomes in 15 (28%) of 54 infants (95% CI 17-41) of pregnant women infected with Zika virus, but these outcomes appeared to be substantially milder than those observed in the Rio de Janeiro study, 3 causing speculation of possible variation in risk across regions. However, case-control, prospective cohort, and enhanced surveillance investigations have not yet yielded insights on why a small fraction of fetuses of infected mothers develop microcephaly and severe sequelae.…”
Section: Zika Virus and Microcephaly: Where Do We Go From Here?mentioning
confidence: 94%
“…Similarly, for infections with WNV, which is estimated to have infected 7 million people in the USA [11,12], the predominate infection outcome is asymptomatic with CDC reporting infection of >46,000 people and more than 2,000 fatalities [12][13][14][15][16][17][18]. The closely related Zika virus, first identified in Uganda in 1947 [19], has recently expanded to South America leading to widespread infection including Guillain-Barré syndrome and more than 6,700 cases of microcephaly and neurological abnormalities in newborns [20][21][22][23][24][25]. As for the other flaviviruses, the majority of infected individuals are asymptomatic or develop mild disease, however Zika virus has been shown to infect fetal brains and neurons and lead to cell death and microcephaly [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%